2008
DOI: 10.3181/0710-rm-279
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α-Actinin-1 in Human Glomerular Mesangial Cells In Vivo and In Vitro

Abstract: Recent studies have demonstrated important roles of alpha-actinins in glomerular disease, while little information is known about the expression profile of alpha-actinins in human glomerular mesangial cells. Here, immunofluorescence and confocal microscopy showed that alpha-actinin-1 exclusively distributed along mesangial cells in human glomeruli of IgA nephropathy. RT-PCR and Western blot further confirmed the expression of alpha-actinin-1 in primary cultured human mesangial cells. We also found that transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Isolation of primary human renal glomerular mesangial cells (HMC) was done previously [37;38]. For this study cells were taken from previously prepared frozen stock and were maintained in RPMI 1640 containing 16.7% FBS and 100ug/ml penicillin and streptomycin as previously described [37;38].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of primary human renal glomerular mesangial cells (HMC) was done previously [37;38]. For this study cells were taken from previously prepared frozen stock and were maintained in RPMI 1640 containing 16.7% FBS and 100ug/ml penicillin and streptomycin as previously described [37;38].…”
Section: Methodsmentioning
confidence: 99%
“…For this study cells were taken from previously prepared frozen stock and were maintained in RPMI 1640 containing 16.7% FBS and 100ug/ml penicillin and streptomycin as previously described [37;38]. HMC at passages 5 through 8 were used.…”
Section: Methodsmentioning
confidence: 99%
“…α-actinin-1 regulates gene expression, thus accelerating ECM accumulation in glomerular disease (40). α-actinin-1 has been documented to be a prognostic factor in leiomyosarcoma survival (24).…”
Section: Discussionmentioning
confidence: 99%
“…Another downregulated protein is α-actinin-1, an actinbinding protein with multiple roles in different cell types (40), including the connection between the cytoskeleton and diverse signaling pathways (41). α-actinin-1 regulates gene expression, thus accelerating ECM accumulation in glomerular disease (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PAI-1 is also a component of the ECM, where it seems to bind tightly to the somatomedin B domain of vitronectin [42] . In pathological conditions in vivo, human mesangial cells overexpress PAI-1, and this upregulation may be related to the stimulation by various cytokines or growth factors such as TNF-␣ [43] and TGF-␤ [44] . In the present study, we have found the molecular mechanisms involved in a beneficial effect that PARP-1 inhibition decreased Ang II-induced upregulation of PAI-1 and FN expression in cultured RMCs.…”
Section: Discussionmentioning
confidence: 99%